Application of Binary Firefly Algorithm (BFA) in tuning PID parameters for couple tank system - Azahar, Arman Hadi; Samsudin, Adam; Yep, Kow Wai; Zainal Abidin, Amar Faiz; Rifin, Rozi; Harun, Mohammad Haniff; Karis, Mohd. Safirin; Azmi, Ezzatul Farhain; Mohd. Nordin, Ili Najaa Aimi (Asian Research Publishing Network (ARPN), 2021)
This paper presents the application of the Binary Firefly Algorithm (BFA) in tuning PID parameters for a coupled tank system. The agent position in the BFA represents the potential combination the PID parameters. This agent position is modelled using a string of 32 binary bits where each eight bits represents the value of